(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Depression is a common but often underdiagnosed comorbidity among patients undergoing maintenance hemodialysis. It significantly impacts treatment adherence, quality of life, and clinical outcomes. Understanding the incidence and contributing factors is essential for early identification and intervention. Objective: To determine the frequency and severity of depression in patients undergoing maintenance hemodialysis and to identify associated demographic and clinical factors. A cross-sectional study was conducted in the Nephrology Department of Shifa International Hospital, Islamabad, over six months. A total of 183 patients aged 30–80 years on maintenance hemodialysis were enrolled using non-probability consecutive sampling. Data were collected through a structured proforma, and depression severity was measured using the Beck Depression Inventory (BDI). Sociodemographic and clinical information was recorded. Data analysis was performed in SPSS version 20 using descriptive statistics and chi-square test, with p ≤ 0.05 considered significant. Results: The mean age of patients was 54.72 ± 14.78 years, and the average duration of hemodialysis was 33.31 ± 16.69 months. The mean BDI score was 12.55 ± 7.07. Depression was present in 128 patients (69.9%), with 27.3% having mild, 24.0% moderate, and 18.6% severe depression. Among all variables assessed, only marital status showed a statistically significant association with depression (p = 0.030), while age, gender, residence, education, comorbidities, and dialysis duration were not significantly associated. Conclusion: Depression is highly prevalent in patients on maintenance hemodialysis, with marital status emerging as a significant associated factor. Routine psychological evaluation should be integrated into dialysis care.